Metal magnetic powder core preparation process for improving high-frequency magnetic performance
Fe powders of different fineness were prepared by ball milling, and combined with chemical precipitation method and insulating coating technology of epoxy modified silicone resin, the problem of large eddy current loss of Fe powder at high frequency was solved, and low magnetic loss and high thermal stability of soft magnetic materials were achieved.
Patent Information
- Application Number
- CN202411952383.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, Fe powder is prone to severe eddy current loss due to its small resistivity at high frequency, resulting in large magnetic loss, and the thermal stability of organic coating agents is poor, affecting the performance of the magnetic powder core.
Fe powders of different fineness were prepared by ball milling, and mixed powders of SiO2 and Fe powder were generated by chemical precipitation. Then, insulating coating was used with epoxy modified silicone resin, and pressing and heat treatment were performed to obtain a metal magnetic powder core with good magnetic properties.
It effectively reduces the magnetic loss of soft magnetic materials, improves its high-frequency magnetic properties, and ensures the thermal stability of the insulating coating layer through the use of modified silicone resin.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal soft magnetic materials, in particular to a preparation process of a metal magnetic powder core for improving high-frequency magnetic properties. Background Art
[0002] With the rapid development of electronic information technology, electronic equipment is constantly developing in the direction of high frequency, high efficiency and miniaturization, which requires soft magnetic composite materials to have lower magnetic loss at high frequency and good DC bias performance under high current. Under high frequency conditions, the eddy current loss of soft magnetic composite materials will rise sharply with the increase of frequency; therefore, reducing the eddy current loss of soft magnetic composite materials at high frequency is the key to reducing its magnetic loss. Eddy current loss is caused by eddy currents generated inside and between magnetic particles under an alternating magnetic field. The former is called intra-particle eddy current, which is related to the resistivity of the magnetic matrix itself. The larger the resistivity, the smaller the eddy current generated. The latter is called inter-particle eddy current, which is related to the insulation between magnetic particles. The better the insulation between magnetic particles, the more the conductive path between particles is isolated, thereby reducing the eddy current between magnetic particles. Therefore, the key to preparing high-frequency and low-magnetic-loss soft magnetic composite materials is to select a magnetic matrix with higher resistivity and to insulate the magnetic matrix.
[0003] Specifically, inductor components are mainly composed of magnetic cores and windings. The magnetic properties and dielectric properties of the magnetic cores; especially the frequency characteristics of the effective magnetic permeability ue and the power loss Pcv, these two properties significantly affect the energy transfer efficiency of the inductor components. Therefore, soft magnetic materials are the key to determining the performance of inductor components. In order to give full play to the potential of high-frequency power electronic products in terms of efficiency, size, weight and power, the magnetic cores for inductors must strike a balance between high saturation magnetization and low core loss characteristics. Traditional soft magnetic materials have significant eddy current effects and high losses at high frequencies; the saturation magnetization of soft ferrites is low and cannot be used as inductor core materials for high current power supplies; it is necessary to improve and optimize its preparation process.
[0004] Based on this, Chinese patent CN101678451B discloses a metal powder for pressed powder magnetic cores and a method for manufacturing pressed powder magnetic cores; it is achieved by heating pure iron powder with a diameter of 10 to 500 μm and a purity of 99 mass % or more to a temperature range of 600°C to 1400°C, and concentrating the Si concentration from the surface of the pure iron powder to a depth of 5 μm through a gas phase reaction within the temperature range, so that the average Si concentration in the depth range is 0.05 mass % to 2 mass %, thereby obtaining a metal powder for pressed powder magnetic cores that improves the adhesion between the insulating material and the particles and improves the electrical insulation without causing a deterioration in compressibility; moreover, the pressed powder magnetic core obtained by this preparation method can have a higher saturation magnetic flux density and low iron loss.
[0005] However, the soft magnetic material process disclosed in the prior art still has the technical problem of large magnetic loss. Specifically, Fe powder has high saturation magnetization and magnetic permeability, and is currently the most widely used metal soft magnetic powder. However, its resistivity is small, and it is easy to generate strong eddy currents at high frequencies, causing serious eddy current losses, thereby reducing the magnetic properties of the material. Therefore, insulating and coating Fe powder to increase its resistivity and reduce its magnetic loss at high frequencies is of great significance for expanding its application at high frequencies. At present, in the technical solutions disclosed in the prior art, organic coating agents are mostly used when insulating and coating Fe powder; however, organic coating agents have the defect of poor thermal stability, and are prone to losses during the heat treatment process, thereby causing leakage and other phenomena.
[0006] Generally, the preparation process of metal magnetic powder core includes four core steps: preparation of magnetic powder, insulation coating process of magnetic powder, pressing molding process and heat treatment process. During the pressing process, the composite powder particles generate a large amount of internal stress due to mutual extrusion. In order to eliminate the generated internal stress and improve the magnetic properties and mechanical strength of the soft magnetic composite material, the pressed green compact needs to be subjected to corresponding heat treatment. Therefore, in the insulation coating process, how to obtain an insulating coating layer with good thermal stability is an important measure to prevent the final magnetic powder core from having large magnetic losses. Summary of the invention
[0007] Based on this, it is necessary to provide a metal magnetic powder core preparation process with improved high-frequency magnetic properties in order to improve the technical problem of how to improve the large magnetic loss in the metal soft magnetic material process.
[0008] A process for preparing a metal magnetic powder core with improved high-frequency magnetic properties comprises the following steps, measured by weight: S1: 55 portions of Fe powder prepared by a gas atomization method are prepared in advance, and are ground by a ball mill to obtain Fe powder with a fineness of 100 mesh and Fe powder with a fineness of 300 mesh respectively; then, the prepared Fe powders are proportioned according to different finenesses so that the 100-mesh Fe powder accounts for 8wt% to 32wt% of the total mass of the 100-mesh powder and the 300-mesh powder, and the two powders of fineness are stirred and mixed uniformly; S2: After washing the mixed powder with anhydrous ethanol, the mixed powder is placed in a reactor; then, 350 parts of anhydrous ethanol is added to the reactor, and mechanical stirring is started in the reactor to evenly disperse the Fe powder in the reactor; then, 5 parts of deionized water and 2 parts of coupling agent are added to the reactor, and stirring is continued for half an hour; S3: adding a preset amount of NH3·H2O to the reactor to control the pH value of the solution in the reactor to be in the range of 9-10; then, slowly adding a preset proportion of ethyl orthosilicate, and after the addition is completed, continuing to stir in the reactor for 3 hours to allow the reaction to proceed fully; S4: After the stirring is completed, the powder in the reaction kettle is filtered out, and the powder is repeatedly washed with anhydrous ethanol until the pH value is 7, and then the powder is filtered out, and the powder is dried at 100° C. for 2 hours under a vacuum environment, and then taken out for use; S5: Add 0.5wt% of epoxy-modified silicone resin and 1 part of phenolic amine epoxy curing agent into the container and dissolve them in a preset amount of acetone solution, and dissolve them by ultrasound; then take 4 parts of the powder dried in step S4 into the aforementioned container, stir them thoroughly and dry the mixture; S6: The mixed dry powder is pressed into a ring-shaped product in a preset mold at a preset pressure for 10 seconds. Then, the ring-shaped product is placed in a tube furnace for heat treatment for 2 hours under an argon atmosphere. After being taken out, the metal magnetic powder core product can be obtained.
[0009] Specifically, in the aforementioned step S1, the specific steps of grinding Fe powder using the ball milling method are as follows: S11: placing Fe powder to be ground into a ball mill according to a preset ratio; S12: The powder was ball-milled with agate balls and 304 stainless steel beads at 150 rpm for 16 h; S13: The ball-milled powder is sieved through a 100-mesh sieve and a 300-mesh sieve to obtain 100-mesh and 300-mesh Fe powders for later use.
[0010] Specifically, in the aforementioned step S2, the coupling agent is silane coupling agent KH-500 or KH-550.
[0011] Specifically, in the aforementioned step S3, the amount of ethyl orthosilicate added is 8 parts.
[0012] Specifically, in the aforementioned step S5, the preparation method of the epoxy-modified silicone resin is: S11: adding a preset amount of epoxy resin 6101 and toluene into a reactor, and dissolving the epoxy resin 6101 in the toluene; S12: The temperature in the reactor is raised to 120° C. to cause reflux, and a preset amount of catalyst is added thereto; S13: adding silicone resin SAR-665 and coupling agent KH-550 according to a preset ratio; S14: removing water generated by the condensation reaction under reduced pressure; S15: The reaction is carried out at a constant temperature of 120° C. for 4 hours to obtain an epoxy-modified silicone resin.
[0013] Specifically, in the aforementioned preparation method of epoxy-modified silicone resin, the feeding ratio of each material is: 55 parts of epoxy resin 6101, 85 parts of toluene, 3 parts of catalyst, 40 parts of silicone resin SAR-665, and 2 parts of coupling agent.
[0014] Specifically, the catalyst used in step S12 is dibutyltin dilaurate.
[0015] Specifically, in step S6, the specific method of heat treatment is: placing the pressed product in a tubular furnace, introducing argon as a protective atmosphere, heating the temperature to 400°C at a rate of 10°C / min and then keeping the temperature for 1 hour, then allowing it to cool in the furnace and taking out the product.
[0016] In summary, the present invention provides a process for preparing a metal magnetic powder core with improved high-frequency magnetic properties. First, a ball milling method is used to prepare 100-mesh and 300-mesh iron powders respectively. Then, the two iron powders of fineness are mixed according to a ratio, and a mixed powder of iron powder and SiO2 is obtained by a chemical precipitation method. Then, epoxy-modified silicone resin is used to insulate and coat the mixed powder. After the mixed powder is pressed and heat-treated, a soft magnetic composite material is obtained. The material has good comprehensive magnetic properties and effectively reduces the magnetic loss of the soft magnetic material. Therefore, the present invention provides a process for preparing a metal magnetic powder core with improved high-frequency magnetic properties. It solves the technical problem of how to improve the large magnetic loss of the metal soft magnetic material process. DETAILED DESCRIPTION
[0017] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0018] Specifically, the present invention provides a process for preparing a metal magnetic powder core with improved high-frequency magnetic properties, which comprises the following steps, measured by weight: S1: 55 portions of Fe powder prepared by a gas atomization method are prepared in advance, and are ground by a ball mill to obtain Fe powder with a fineness of 100 mesh and Fe powder with a fineness of 300 mesh respectively; then, the prepared Fe powders are proportioned according to different finenesses so that the 100-mesh Fe powder accounts for 8wt% to 32wt% of the total mass of the 100-mesh powder and the 300-mesh powder, and the two powders of fineness are stirred and mixed uniformly; S2: After washing the mixed powder with anhydrous ethanol, the mixed powder is placed in a reactor; then, 350 parts of anhydrous ethanol is added to the reactor, and mechanical stirring is started in the reactor to evenly disperse the Fe powder in the reactor; then, 5 parts of deionized water and 2 parts of coupling agent are added to the reactor, and stirring is continued for half an hour; S3: adding a preset amount of NH3·H2O to the reactor to control the pH value of the solution in the reactor to be in the range of 9-10; then, slowly adding a preset proportion of ethyl orthosilicate, and after the addition is completed, continuing to stir in the reactor for 3 hours to allow the reaction to proceed fully; S4: After the stirring is completed, the powder in the reaction kettle is filtered out, and the powder is repeatedly washed with anhydrous ethanol until the pH value is 7, and then the powder is filtered out, and the powder is dried at 100° C. for 2 hours under a vacuum environment, and then taken out for use; S5: Add 0.5wt% of epoxy-modified silicone resin and 1 part of phenolic amine epoxy curing agent into the container and dissolve them in a preset amount of acetone solution, and dissolve them by ultrasound; then take 4 parts of the powder dried in step S4 into the aforementioned container, stir them thoroughly and dry the mixture; S6: The mixed dry powder is pressed into a ring-shaped product in a preset mold at a preset pressure for 10 seconds. Then, the ring-shaped product is placed in a tube furnace for heat treatment for 2 hours under an argon atmosphere. After being taken out, the metal magnetic powder core product can be obtained.
[0019] Specifically, in the aforementioned step S1, the specific steps of grinding Fe powder using the ball milling method are as follows: S11: placing Fe powder to be ground into a ball mill according to a preset ratio; S12: The powder was ball-milled with agate balls and 304 stainless steel beads at 150 rpm for 16 h; S13: The ball-milled powder is sieved through a 100-mesh sieve and a 300-mesh sieve to obtain 100-mesh and 300-mesh Fe powders for later use.
[0020] Furthermore, in the aforementioned step S2, the coupling agent is silane coupling agent KH-500 or KH-550.
[0021] Furthermore, in the aforementioned step S3, the input amount of NH3·H2O is about 1-3 parts, and the operation should be regulated according to the monitored pH value of the solution.
[0022] Furthermore, in the aforementioned step S3, the amount of ethyl orthosilicate added is 8 parts.
[0023] Furthermore, in the aforementioned step S5, the preparation method of the epoxy-modified silicone resin is: S11: adding a preset amount of epoxy resin 6101 and toluene into a reactor, and dissolving the epoxy resin 6101 in the toluene; S12: The temperature in the reactor is raised to 120° C. to cause reflux, and a preset amount of catalyst is added thereto; S13: adding silicone resin SAR-665 and coupling agent KH-550 according to a preset ratio; S14: removing water generated by the condensation reaction under reduced pressure; S15: The reaction is carried out at a constant temperature of 120° C. for 4 hours to obtain an epoxy-modified silicone resin.
[0024] Specifically, in the aforementioned step S12, the catalyst used may be dibutyltin dilaurate.
[0025] In the preparation method of epoxy-modified silicone resin, the feeding ratio of each material is as follows: 55 parts of epoxy resin 6101, 85 parts of toluene, 3 parts of catalyst, 40 parts of silicone resin SAR-665, and 2 parts of coupling agent, calculated by mass.
[0026] Furthermore, the following is an example of the feeding of Fe powders of different finenesses in a process for preparing a metal magnetic powder core for improving high-frequency magnetic properties of the present invention, measured by mass: Comparative Example 1: 0 parts of 100-mesh Fe powder and 100 parts of 300-mesh Fe powder.
[0027] Example 1: 8 parts of 100-mesh Fe powder and 92 parts of 300-mesh Fe powder.
[0028] Example 2: 15 parts of 100-mesh Fe powder and 85 parts of 300-mesh Fe powder.
[0029] Example 3: 25 parts of 100-mesh Fe powder and 75 parts of 300-mesh Fe powder.
[0030] Example 4: 32 parts of 100-mesh Fe powder and 68 parts of 300-mesh Fe powder.
[0031] Specifically, Fe powder has high saturation magnetization and magnetic permeability, but its resistivity is small, and it is easy to generate strong eddy current at high frequency, which is easy to cause serious eddy current loss. Therefore, insulating and coating Fe powder to improve its resistivity is an important technical means to improve its magnetic properties at high frequency. Among them, SiO2 has high resistivity and good thermal stability, and is a more ideal insulating coating agent. In addition, since metal and oxide are a kind of heterogeneous interface, the bonding ability between the interfaces determines the coating effect of the powder and the stability of the material properties. Therefore, the present invention adopts a chemical precipitation method to generate SiO2, and the iron powder and SiO2 mixed powder are insulated and coated with epoxy-modified silicone resin.
[0032] Considering that the soft magnetic properties and magnetic loss of the Fe-Si-based soft magnetic composite material mainly depend on the quality of the insulating structure in the Fe-Si-based soft magnetic composite material. A good insulating structure not only requires good uniformity of the coating layer to avoid local direct contact of magnetic powders leading to reduced resistance characteristics, and reduce the introduction of excess coating materials leading to reduced soft magnetic characteristics, but also requires a high intrinsic resistivity of the coating layer to achieve high insulation between magnetic powders, thereby significantly reducing high-frequency magnetic losses; therefore, the present invention adopts ball milling to obtain iron powders of different finenesses and proportions them according to a preset ratio to improve the uniformity between the iron powder and the inorganic coating layer.
[0033] Therefore, in a metal magnetic powder core preparation process for improving high-frequency magnetic properties of the present invention, the resistivity of the magnetic powder core can be improved by introducing the non-metallic element Si to form an F-Si alloy, and the magnetic powder core loss is lower than that of pure iron powder, and it can also have excellent DC bias performance. In addition, compared with flaky and irregular particles, spherical particles have better processing performance. The powder surface can form a complete and uniform insulating layer, which is beneficial to improving the resistivity. Further, compared with flaky and irregular particles, spherical particles have better processing performance. The powder surface can form a complete and uniform insulating layer, which is beneficial to improving the resistivity. Considering the close relationship between powder particle size and magnetic properties, the present invention can effectively optimize the magnetic properties of the powder by adjusting the bulk density of the powder, the powder particle size distribution and the quality of the binder.
[0034] Specifically, the soft magnetic properties of the aforementioned embodiments are shown in Table 1 below: Table 1: Summary of soft magnetic properties test parameters
[0035] Specifically, the density can be increased by adding an appropriate amount of 10-mesh fine iron powder to embed it into the gaps of 300-mesh coarse powder to obtain a higher magnetic permeability. After that, as the content of 100-mesh iron powder increases, the magnetic permeability and saturation magnetization of the magnetic powder core increase, but if the fine iron powder is added excessively, the filling of the coarse powder gap has reached saturation, and new gaps will form between the fine powders, which will deteriorate the magnetic properties. Therefore, when the addition amount of 100-mesh iron powder is 25wt%, the magnetic powder core obtained has the highest magnetic permeability and saturation magnetization.
[0036] Furthermore, if the content of epoxy-modified silicone resin is too low, the magnetic powder coating is incomplete, which is not conducive to suppressing eddy current loss; while if the content of epoxy-modified silicone resin is too high, the spacing between the magnetic powders increases, which reduces the magnetic permeability. In the present invention, when the resin content is 0.5wt%, a balance point is reached between the magnetic permeability and the loss, and a higher magnetic permeability is obtained while ensuring lower losses, and the magnetic powder core has a maximum quality factor.
[0037] Furthermore, if the pressure is too low during molding, the magnetic powder is not compacted, resulting in a large distance between particles, many gaps inside the magnetic powder core, low magnetic permeability and high loss; if the pressure is too high, the particles are broken, which is not conducive to obtaining excellent magnetic properties. In the aforementioned step S6, the holding pressure during pressing is 1200MPa.
[0038] Furthermore, the internal stress introduced during the molding process will hinder the magnetization process and increase the hysteresis loss. Therefore, high-temperature heat treatment is required. The resin is easy to decompose at high temperature, damage the insulating layer, and increase the eddy current loss. Therefore, an appropriate annealing temperature is required. Therefore, in step S6, the specific method of heat treatment is: place the pressed product in a tubular furnace, introduce argon as a protective atmosphere, heat it to 400°C at a rate of 10°C / min, keep it warm for 1 hour, and then cool it with the furnace to take out the product.
[0039] In summary, the present invention provides a process for preparing a metal magnetic powder core with improved high-frequency magnetic properties. First, a ball milling method is used to prepare 100-mesh and 300-mesh iron powders respectively. Then, the two iron powders of fineness are mixed according to a ratio, and a mixed powder of iron powder and SiO2 is obtained by a chemical precipitation method. Then, epoxy-modified silicone resin is used to insulate and coat the mixed powder. After the mixed powder is pressed and heat-treated, a soft magnetic composite material is obtained. The material has good comprehensive magnetic properties and effectively reduces the magnetic loss of the soft magnetic material. Therefore, the present invention provides a process for preparing a metal magnetic powder core with improved high-frequency magnetic properties. It solves the technical problem of how to improve the large magnetic loss of the metal soft magnetic material process.
[0040] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0041] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A process for preparing a metal magnetic powder core with improved high-frequency magnetic properties, characterized in that: By weight, it comprises the following steps: S1: 55 portions of Fe powder prepared by a gas atomization method are prepared in advance, and are ground by a ball mill to obtain Fe powder with a fineness of 100 mesh and Fe powder with a fineness of 300 mesh respectively; then, the prepared Fe powders are proportioned according to different finenesses so that the 100-mesh Fe powder accounts for 8wt% to 32wt% of the total mass of the 100-mesh powder and the 300-mesh powder, and the two powders of fineness are stirred and mixed uniformly; S2: After washing the mixed powder with anhydrous ethanol, the mixed powder is placed in a reactor; then, 350 parts of anhydrous ethanol is added to the reactor, and mechanical stirring is started in the reactor to evenly disperse the Fe powder in the reactor; then, 5 parts of deionized water and 2 parts of coupling agent are added to the reactor, and stirring is continued for half an hour; S3: adding a preset amount of NH3·H2O to the reactor to control the pH value of the solution in the reactor to be in the range of 9-10; then, slowly adding a preset proportion of ethyl orthosilicate, and after the addition is completed, continuing to stir in the reactor for 3 hours to allow the reaction to proceed fully; S4: After the stirring is completed, the powder in the reaction kettle is filtered out, and the powder is repeatedly washed with anhydrous ethanol until the pH value is 7, and then the powder is filtered out, and the powder is dried at 100° C. for 2 hours under a vacuum environment, and then taken out for use; S5: Add 0.5wt% of epoxy-modified silicone resin and 1 part of phenolic amine epoxy curing agent into the container and dissolve them in a preset amount of acetone solution, and dissolve them by ultrasound; then take 4 parts of the powder dried in step S4 into the aforementioned container, stir them thoroughly and dry the mixture; S6: The mixed dry powder is pressed into a ring-shaped product in a preset mold at a preset pressure for 10 seconds. Then, the ring-shaped product is placed in a tube furnace for heat treatment for 2 hours under an argon atmosphere. After being taken out, the metal magnetic powder core product can be obtained.
2. The process for preparing a metal magnetic powder core with improved high-frequency magnetic properties according to claim 1, characterized in that: In the aforementioned step S1, the specific steps of grinding Fe powder using ball milling are as follows: S11: placing Fe powder to be ground into a ball mill according to a preset ratio; S12: The powder was ball-milled with agate balls and 304 stainless steel beads at 150 rpm for 16 h; S13: The ball-milled powder is sieved through a 100-mesh sieve and a 300-mesh sieve to obtain 100-mesh and 300-mesh Fe powders for later use.
3. The process for preparing a metal magnetic powder core with improved high-frequency magnetic properties according to claim 1, characterized in that: In the aforementioned step S2, the coupling agent is silane coupling agent KH-500 or KH-550.
4. The process for preparing a metal magnetic powder core with improved high-frequency magnetic properties according to claim 1, characterized in that: In the aforementioned step S3, the amount of ethyl orthosilicate added is 8 parts.
5. The process for preparing a metal magnetic powder core with improved high-frequency magnetic properties according to claim 1, characterized in that: In the aforementioned step S5, the preparation method of the epoxy-modified silicone resin is: S11: adding a preset amount of epoxy resin 6101 and toluene into a reactor, and dissolving the epoxy resin 6101 in the toluene; S12: The temperature in the reactor is raised to 120° C. to cause reflux, and a preset amount of catalyst is added thereto; S13: adding silicone resin SAR-665 and coupling agent KH-550 according to a preset ratio; S14: removing water generated by the condensation reaction under reduced pressure; S15: The reaction is carried out at a constant temperature of 120° C. for 4 hours to obtain an epoxy-modified silicone resin.
6. The process for preparing a metal magnetic powder core with improved high-frequency magnetic properties according to claim 5, characterized in that: In the preparation method of epoxy-modified silicone resin, the feeding ratio of each material is: 55 parts of epoxy resin 6101, 85 parts of toluene, 3 parts of catalyst, 40 parts of silicone resin SAR-665, and 2 parts of coupling agent.
7. The process for preparing a metal magnetic powder core with improved high-frequency magnetic properties according to claim 5, characterized in that: The catalyst used in step S12 is dibutyltin dilaurate.
8. The process for preparing a metal magnetic powder core with improved high-frequency magnetic properties according to claim 1, characterized in that: In step S6, the specific method of heat treatment is: placing the pressed product in a tubular furnace, introducing argon as a protective atmosphere, heating the temperature to 400°C at a rate of 10°C / min and then keeping the temperature for 1 hour, then allowing it to cool in the furnace and taking out the product.
Citation Information
Patent Citations
Metallic powder for powder magnetic core and process for producing powder magnetic core
CN101678451B
Method for preparing high frequency soft magnetic iron-silicon-aluminum magnetic powder cores
CN108777229A
Integrated co-fired inductor as well as preparation method and application thereof
CN112735797A
Preparation method of low-loss iron-silicon-aluminum-based composite soft magnetic powder core
CN114551021A
Low-loss soft magnetic composite material for high frequency and high power and preparation method thereof
CN115312316A